2020
DOI: 10.3892/mmr.2020.11325
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of miR‑532‑3p contributes to cerebral ischemia/reperfusion oxidative stress injury by directly targeting NOX2

Abstract: NADPH oxidase 2 (NOX2) is a major subtype of NOX and is responsible for the generation of reactive oxygen species (ROS) in brain tissues. MicroRNAs (miRNAs/miRs) are important epigenetic regulators of NOX2. The present study aimed to identify the role of NOX2 miRNA-targets in ischemic stroke (IS). A rat cerebral ischemia/reperfusion (CI/R) injury model and a SH-SY5Y cell hypoxia/reoxygenation (H/R) model were used to simulate IS. Gene expression levels, ROS production and apoptosis in tissue or cells were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“… 33 miR‑532‑3p downregulation leads to oxidative stress injury following cerebral ischemia/reperfusion by targeting NOX2 directly. 34 In the present study, we also observed that the neuroprotective functions mediated by miR-126a-5p in ischemic brain injury were noticeably antagonized by NOX2 overexpression, suggesting NOX2 overexpression and its upstream regulator miR-126a-5p could synergistically modulate oxidative stress and apoptosis. Our results indicated that upregulated miR-126a-5p could suppress oxidative stress and apoptosis through targeting NOX2 directly.…”
Section: Discussionsupporting
confidence: 76%
“… 33 miR‑532‑3p downregulation leads to oxidative stress injury following cerebral ischemia/reperfusion by targeting NOX2 directly. 34 In the present study, we also observed that the neuroprotective functions mediated by miR-126a-5p in ischemic brain injury were noticeably antagonized by NOX2 overexpression, suggesting NOX2 overexpression and its upstream regulator miR-126a-5p could synergistically modulate oxidative stress and apoptosis. Our results indicated that upregulated miR-126a-5p could suppress oxidative stress and apoptosis through targeting NOX2 directly.…”
Section: Discussionsupporting
confidence: 76%
“…It was recently reported that the miRNAs were involved in progression of CI/R [ 7 , 15 , 16 ]. In the present study, we found that the progression of CI/R is significantly suppressed by miR-27a-3p mimics.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding RNAs involved in the development of multiple diseases, including CI/R [ 4 6 ]. For instance, miR-532-3p downregulation is known to aggravate CI/R injury by targeting NOX2 [ 7 ], and Zuo et al showed that miR-652 could protect against CI/R injury through suppression of NOX2 [ 8 ]. In addition, MiR-27a-3p is reportedly involved in the progression of ischemia/reperfusion (I/R) injury [ 9 ], though the biological function of miR-27a-3p in CI/R remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro H9C2 cell H/R model was established following the methods of Mao et al to mimic myocardial ischemia reperfusion injury [ 16 ]. When cells grow to a 70% area of a plate, the DMEM culture was removed and cells were washed twice using PBS to remove the residual culture.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter assay was performed following the methods of Mao et al to observe the interaction between PTEN and miR-129 [ 16 ]. A luciferase reporter gene plasmid (pGL6; Promega Corporation) was constructed and designated as PTEN-WT or PTEN-MU according to the sequence of 3′UTR of PTEN cloned into the plasmid whether it contains the wild-type (WT) binding sites of miR-129-5p“CAAAAAA” or mutant (MUT)“CAAGAAA”.…”
Section: Methodsmentioning
confidence: 99%